Genome-wide analyses of lung cancer after single high-dose radiation at five time points (2, 6, 12, 24, and 48 h) - Du, Yajing; Zheng, Yunna; Yu, Kaiwen; Zhan, Cheng; Qiao, Tiankui (Frontiers in Genetics, 2023)
Background: An increasing number of clinicians are experimenting with high-dose radiation. This study focuses on the genomic effects of high-dose single-shot radiotherapy and aims to provide a dynamic map for non-small cell lung cancer (NSCLC). Methods: We used whole-transcriptome sequencing to understand the evolution at molecular levels in A549 and H1299 exposed to 10 Gy X-rays at different times (2, 6, 12, 24, and 48 h) in comparison with the no radiation group. Ingenuity pathway analysis, ceRNA analysis, enrichment analysis, and cell cycle experiments are performed for molecular analyses and function analyses. Results: Whole-transcriptome sequencing of NSCLC showed a significant dynamic change after radiotherapy within 48 h. MiR-219-1-3p and miR-221-3p, miR-503-5p, hsa-miR-455-5p, hsa-miR-29-3p, and hsa-miR-339-5p were in the core of the ceRNA related to time change. GO and KEGG analyses of the top 30 mRNA included DNA repair, autophagy, apoptosis, and ferroptosis pathways. Regulation of the cell cycle-related transcription factor E2F1 might have a key role in the early stage of radiotherapy (2.6 h) and in the later stage of autophagy (24 and 48 h). Functions involving different genes/proteins over multiple periods implied a dose of 10 Gy was related to the kidney and liver pathway. Radiation-induced cell cycle arrest at the G2/M phase was evident at 24 h. We also observed the increased expression of CCNB1 at 24 h in PCR and WB experiments. Conclusion: Our transcriptomic and experimental analyses showed a dynamic change after radiation therapy in 48 h and highlighted the key molecules and pathways in NSCLC after high-dose single-shot radiotherapy.